Penerapan Nilai Islam Moderat melalui Pembelajaran Ke-Nu-an dalam Mewujudkan Sikap Moderat Peserta Didik - Khafifi, Bagus Farhan; Anggraeni, Dewi (Fakultas Keguruan dan Ilmu Pendidikan Universitas Nahdatul Ulama Indonesia, 2024)
Radicalism makes religion a propaganda tool for social change or drastic political reform by using violent means. The value of moderate Islam is important to be applied to realize the moderate attitude of students. The research was conducted using an approach with the type of field research at MTs Ma'arif NU 05 Majasari which is one of the educational institutions under NU, has a spirit in realizing moderate Islam. The results of this study reveal that; 1) the formation of moderate attitudes begins with a moderate understanding of Islam in line with the values of Islam Rahmatan lil Alamin, 2) Ke-NU-an learning contains the content of moderate Islamic values taught, namely tawasuth, tawazun, i'tidal, and tasamuh. The learning process is not only taught theoretically but also applicatively through practices that are in line with the value of religious moderation, Students' moderate character formation is carried out not only in learning but also through extracurricular activities, religious habituation, group learning strategies, exemplary approaches, motivation and compassion. This research makes a real contribution to the development of an educational model that is able to produce young people who are ready to face global challenges with a moderate attitude through specialty curriculum content.